ENHANCED PHOTOCATALYTIC DEGRADATION OF NAPHTHALIMIDE-BASED ACID DYES USING Cu/Ag Co-DOPED TiO2 NANOCATALYST OPTIMIZED BY RESPONSE SURFACE METHODOLOGY - Mustapha, Amina Muhammad; Giwa, Abdulraheem; Salami, Umar Ameuru; Danladi, Eli (FUDMA JOURNAL OF SCIENCES, 2025)
The environmental persistence and toxicity of synthetic dyes, particularly emerging naphthalimide derivatives, necessitates advanced degradation technologies. This work investigates the photocatalytic degradation of two acid naphthalimide-based dyes using a nanocatalyst synthesized by co-doping TiO2 with Cu/Ag via the co-precipitation technique. The co-doped catalyst exhibited superior properties to pure TiO2, including a reduced crystallite size (28.54 nm), a red-shifted absorption edge (430 nm) corresponding to a narrower bandgap (2.24 eV), and a 61.4% increase in BET surface area (138.77 m2/g). Process optimization was carried out using response surface methodology (RSM) with a central composite design (CCD) to evaluate the effects of initial dye concentration, pH, catalyst dosage and reaction time. The developed models showed a strong fit (R2 > 0.93) and closely matched the experimental results, achieving high degradation efficiencies of up to 97.31% for Dye A and 97.01% for Dye B. Kinetic modelling revealed that both dyes followed pseudo-first-order kinetics, with rate constants of 0.0331 min⁻¹ and 0.0266 min⁻¹ and corresponding correlation coefficients (R2 = 0.9713 and 0.9852), indicating surface-limited degradation processes. Substantial mineralization was supported by the Chemical Oxygen Demand (COD) analysis and reductions of 70.0 % and 77.5 % of Dye A and Dye B respectively.